Electric field probe calibration method by using a TEM cell for reference field generation - Ben-Hassine Seif; Lerat Jean-Marie (EPJ Web of Conferences)
The article presents a method to calibrate electric field probes using a transverse electromagnetic (TEM) cell as a reference. The TEM cell generates uniform and repeatable fields for accurate calibration. The process and setup are carefully detailed to ensure precise generation and measurement. We perform a full uncertainty analysis, considering factors like power delivery, septum-to-wall distance, impedance mismatch, and field inhomogeneity. The total uncertainty of the calibration is 10 % of the electric field amplitude, ensuring good accuracy. To validate the method, measurements are compared with data from an accredited laboratory over a frequency range of 9 kHz to 300 MHz. The results show excellent agreement, with errors within acceptable limits. This confirms the reliability and robustness of the method. The proposed approach provides a reliable solution for accurate electric field probe calibration.